Fetal Growth Is Associated with Maternal Fasting Plasma Glucose at First Prenatal Visit - Liu, Bin; Chen, Haitian; Xu, Yun; An, Chongyou; Zhong, Lieqiang; Wang, Xiaohui; Zhang, Ying; Chen, Hanqing; Zhang, Jinxin; Wang, Zilian (PloS one, 2014)
Fasting plasma glucose (FPG) concentration measured at the first prenatal visit is a predictor of gestational diabetes mellitus (GDM); however, whether this test is indicative of fetal growth has not been clarified. Thus, the purpose of this study was to determine whether birth weight and birth length were related to FPG levels at the first prenatal visit. Research samples were collected from pregnant women who took an FPG test at their first prenatal visit (10-24 gestational weeks), received regular prenatal care, and delivered in our center. FPG value, maternal pre-gravid BMI, weight gain before FPG test, before and after Oral Glucose Tolerance Test (OGTT), neonatal birthweight, birth length, Ponderal Index and birthing method were recorded for analysis. Data were analyzed by independent sample t test, Pearson correlation, and Chi-square test, followed by partial correlation or logistic regression to confirm differences. Statistical significance level was α = 0.05. 2284 pregnant women, including 462 GDM and 1822 with normal glucose tolerance (NGT) were recruited for the present study. FPG concentration at the first prenatal visit was associated with neonatal birth weight (partial correlation coefficient r' = 0.089, P<0.001) and birth length (partial correlation coefficient r' = 0.061, P = 0.005), but not with Ponderal Index or birthing method. Maternal pre-gravid BMI was associated with FPG value (partial correlation coefficient r' = 0.113, P<0.001). FPG concentration at the first prenatal visit (OR = 2.945, P<0.001), weight gain before OGTT test (OR = 1.039, P = 0.010), and age (OR = 1.107, P<0.001) were independent related factors of GDM. Fasting plasma glucose concentration at the first prenatal visit is associated with fetal growth. Maternal pre-gravid BMI and weight gain are related to glucose metabolism.